(untitled) (Global Journal of Human-Social Science, 2021)
The article examines the contacting languages in regional bilingual environments and their role in the preservation of national identity and national culture in multinational states. Using the example of the regional languages of Spain that have received the status of co-official languages (Basque, Catalan, Galician, Aran and Valencian), the linguistic situation in autonomous entities, the peculiarities of bilingualism and the types of language conflicts are studied. The selected parameters are used to describe the linguistic situation in the Republic of North Ossetia-Alania. The article concludes about the status of the Ossetian language, the dominant role of the Russian language, and the unbalanced linguistic situation 1 . The formation of national -Ossetian -identity should take place in the three-dimensional space of national, all-Russian and world culture.